2009
DOI: 10.1115/1.3072714
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Vane Clocking Effects on Embedded Compressor Stage Performance

Abstract: Previous research has shown that vane clocking, the circumferential indexing of adjacent vane rows with similar vane counts, can be an effective means to increase stage performance, reduce discrete frequency noise, and/or reduce the unsteady blade forces that can lead to high cycle fatigue. The objective of this research was to experimentally investigate the effects of vane clocking in an embedded compressor stage, focusing on stage performance. Experiments were performed in the intermediate-speed Purdue three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…There is a clear increase in vane clocking effectiveness beginning somewhere between the high-design and high-loading conditions, after which the clocking effects decline. These trends support the previous vane clocking studies conducted in this compressor, where vane clocking effects were strongest at a high-loading condition [15], but no measurable changes in stall margin aer associated with vane clocking [1]. …”
Section: Overall Stator 2 Total Pressure Losssupporting
confidence: 89%
See 2 more Smart Citations
“…There is a clear increase in vane clocking effectiveness beginning somewhere between the high-design and high-loading conditions, after which the clocking effects decline. These trends support the previous vane clocking studies conducted in this compressor, where vane clocking effects were strongest at a high-loading condition [15], but no measurable changes in stall margin aer associated with vane clocking [1]. …”
Section: Overall Stator 2 Total Pressure Losssupporting
confidence: 89%
“…Clocking effects at the design point and a high-loading case have been interrogated in detail previously in this facility, and both conditions are known to have measurable and different influences on stator 2 loss [15]. Rather than monotonically increasing as the compressor is loaded to stall, clocking effects decrease as the compressor is loaded to stall, and previous work has shown that the stalling mass flow for different clocking configurations were nearly the same and within the uncertainty of the flow rate measurements [1].…”
Section: Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…A probe configuration with five radial probes (P0) on three instrumented stators around the annulus is schematically shown in Figure 1. The time-mean flow field in a multi-stage axial compressor at design operating conditions is circumferentially non-uniform [4], [7], [12]. The flow field is affected by the wakes from the upstream stator rows and the potential fields of the adjacent stationary components.…”
Section: Introductionmentioning
confidence: 99%
“…6 The experiment in embedded stage of the Purdue Three-Stage Compressor Facility indicated that in the embedded Stage 2 the overall efficiency change induced by the vane clocking was 0.27 points. 7 In addition, the compound-lean stators were adopted in a low speed repeating compressor stage to investigate the strengthened clocking effect, and a maximum efficiency increase of 1.22 points at design condition was obtained. 8 Vane clocking has also been demonstrated to have an effect on the unsteady blade loading.…”
Section: Introductionmentioning
confidence: 99%